1999
DOI: 10.2135/cropsci1999.0011183x003900010028x
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis and Productivity of Cotton under Silverleaf Whitefly Stress

Abstract: The silverleaf whitefly (SLW), Bemisia argentifolii (Bellows and Perring), has been a severe pest of numerous field and vegetable crops for many years. Nevertheless, little has been reported on the complex interactions between SLW and its host plants. This study was aimed at investigating the effects of SLW on cotton (Gossypium hirsutum L.) photosynthesis and productivity under various irrigation and N fertilization regimes. Cotton plants (cv. Siv'on) were examined during an entire growing season in two factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 0 publications
3
23
0
Order By: Relevance
“…Osmotic potential is not affected by SLW (Lin et al 1999a), excluding the possibility of osmoregulation in our case.…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…Osmotic potential is not affected by SLW (Lin et al 1999a), excluding the possibility of osmoregulation in our case.…”
Section: Discussionmentioning
confidence: 40%
“…The silverleaf whitefly (SLW), Bemisia argentifolii Bellows and Perring, is one of the most noxious pests of many field and vegetable crops, causing billions of dollars worth of damage through direct sap feeding and massive deposition of honeydew (Byrne et al 1990, Perring et al 1993, Brown et al 1995. As with other insect injuries, a large reduction in plant dry matter and final yield is commonly reported after SLW infestation (Chu et al 1994, Riley and Palumbo 1995, Lin et al 1999a), which may be partly ascribed to the reduced net photosynthetic rate (P n ) documented in different plant species (Buntin et al 1993, Yee et al 1996, Lin et al 1999a. In tomato (Lycopersicon esculentum Mill.…”
Section: Introductionmentioning
confidence: 99%
“…This induces early defoliation and impacts the soybean plant development and yield, as observed in some soybean fields under attack of this pest (VIEIRA et al, 2011). Another problem is that B. tabaci can cause chlorosis in the leaves of attacked plants, reducing photosynthesis (LIN et al, 1999). However, the number of B. tabaci on the soybean plants that triggers these types of damage is not yet well established.…”
Section: Discussionmentioning
confidence: 99%
“…They also reported that the photosynthetic rate of individual leaves decreased gradually from the top to the bottom for both control and infested plants. Similarly photosynthetic rate decreased 50% at about 60 days after silverleaf whiteXy introduction on cotton (Lin et al 1999a). They also reported that the relative photosynthetic rate (infested/non-infested) was signiWcantly correlated with silverleaf whiteXy adult density on the maximally infested cotton leaf.…”
Section: Leaf Physiologymentioning
confidence: 88%
“…They also reported that the relative photosynthetic rate (infested/non-infested) was signiWcantly correlated with silverleaf whiteXy adult density on the maximally infested cotton leaf. The silverleaf whiteXy infestation has been shown to reduce cotton foliar photosynthetic rates (Shtaynmetz 1990;Yee et al 1996;Lin et al 1999aLin et al , b, 2000. Sato and Kim (1980) found that the net photosynthesis of leaves three, four, and Wve were 60-70, 30-50 and 10%, respectively of Xag leaf in healthy rice plants under Weld conditions.…”
Section: Leaf Physiologymentioning
confidence: 99%